2016
DOI: 10.1111/cas.12857
|View full text |Cite
|
Sign up to set email alerts
|

Report on the use of non‐clinical studies in the regulatory evaluation of oncology drugs

Abstract: Non-clinical studies are necessary at each stage of the development of oncology drugs. Many experimental cancer models have been developed to investigate carcinogenesis, cancer progression, metastasis, and other aspects in cancer biology and these models turned out to be useful in the efficacy evaluation and the safety prediction of oncology drugs. While the diversity and the degree of engagement in genetic changes in the initiation of cancer cell growth and progression are widely accepted, it has become incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…In vivo studies using target tumour cell lines were not conducted for histone deacetylase (HDAC) inhibitors, such as romidepsin (indication: PTCL) and vorinostat (indication: CTCL), which showed tumour growth inhibitory activity using other tumour cell lines. It is reported that HDAC inhibitors are effective against cancer types which expressed high level of HDAC, other than the clinically indicated cancers [ 13 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies using target tumour cell lines were not conducted for histone deacetylase (HDAC) inhibitors, such as romidepsin (indication: PTCL) and vorinostat (indication: CTCL), which showed tumour growth inhibitory activity using other tumour cell lines. It is reported that HDAC inhibitors are effective against cancer types which expressed high level of HDAC, other than the clinically indicated cancers [ 13 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylase (HDAC) inhibitors, such as romidepsin (PTCL) and vorinostat (CTCL), were ineffective during in vivo studies using target carcinomas, but showed tumour growth inhibitory activity using other tumour cell lines. HDAC inhibitors are effective against cancer types other than the clinically indicated cancers (13,45). For vorinostat, the PMDA considered that the suppression of CTCL cell proliferation by the same mechanism as that for colon cancer-derived cells, untargeted cancer, was unclear and required additional in vivo studies using CTCL-derived cell lines; however, there was no discussion of its e cacy in CTCL-derived cells in Europe and the United States.…”
Section: Discussionmentioning
confidence: 99%
“…FDA and EMA have distinct guidelines, whereas there are distinct guidelines in other parts such as Australia, Brazil, Japan, Korea, Singapore, and Taiwan just to give a flavor of the unique differences that pose constraints in the current clinical development of ATMP cell therapy. While such efforts to converge on an unified regulatory process are underway through engagements, two critical issues have been identified to be addressed, the concept of potency assessment as well as in vivo tumorigenicity studies [96].…”
Section: Current Advances and Future Prospectsmentioning
confidence: 99%